Hypochloremia in cats – prevalence and associated diseases - Zeugswetter, Florian K.; Pagitz, Maximilian; Friedrich, Mona Sarah (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2016)
Objective: To describe the prevalence and possible causes of hypochloremia in the local hospital cat population. Material and methods: Retrospective study consisting of two parts. Data were collected from the local electronic medical records database using the search terms „chloride“ and „cats“ (part A), and „blood gas analysis“ and „cats“ (part B). The medical records of the hypochloremic cats were then reviewed to determine prior treatment or infusions and to identify major underlying disease processes. Part A included an age and gender matched non-hypochloremic control group, whereas in part B acid-base status was assessed. Results: Hypochloremia was detected in 367 (27%) of 1363 blood samples. The application of a correction formula to adjust for free water changes decreased the number of hypochloremic cats to 253 (19%). Only a minority had received glucocorticoids or loop diuretics and the prevalence of vomiting was 44%. Common associated disorders were gastrointestinal and respiratory diseases, as well as azotemia and diabetes mellitus. Polyuria/ polydipsia, dehydration, prednisolone or furosemide pretreatment, azotemia and diabetes mellitus increased, whereas fluid therapy and the diagnosis of neoplasia decreased the prevalence of hypochloremia. An inverse correlation was found between corrected chloride and standar dized base excess (rs = –0.597, p = 0.001) as well as anion gap (rs = –0.4, p = 0.026). 99% of the hypochloremic cats had derangements of acid-base balance. Conclusion: Hypochloremia is a common electrolyte disorder in the local cat population. The correction formula is ne cessary to adjust for changes in plasma osmolality. Although associated with metabolic alkalosis, most of the hypochloremic cats have a normal or decreased pH. The inverse correlation of chloride and anion gap als well as the high proportion of azotemic or diabetic animals support the concept of compensatory acidosis induced hypochlor emia. Clinical relevance: Hypochloremia should prompt the clinician to performe blood-gas analysis. Diabetes mellitus (especially ketoacidosis) and renal disease should be included in current algorithms for the evaluation of hypochloremic patients.
Keywords: Chloride; metabolic compensation; electrolyte disorder; algorithm; diabetes mellitus; renal failure